Evaluation of an heterogeneous group of patients with von Willebrand disease using an assay alternative to ristocetin induced platelet agglutination. (27th August 2015) - Stufano, F.; Baronciani, L.; Pagliari, M. T.; Franchi, F.; Cozzi, G.; Garcia‐Oya, I.; Bucciarelli, P.; Boscarino, M.; Peyvandi, F.
Summary Background Diagnosis of von Willebrand disease (VWD) type 2 usually relies on the discrepancy between the von Willebrand factor (VWF) ristocetin cofactor activity (VWF:RCo) and VWF antigen (VWF:Ag). Type 2B patients can be discriminated from other qualitative VWD variants by using ristocetin‐induced platelet agglutination (RIPA) test. The major limitation of RIPA is the requirement of fresh blood sample. Objectives In this study, we evaluated the VWF gain‐of‐function mutant GPIb binding (VWF:GPIbM) and VWF:RCo assays to investigate whether the VWF:GPIbM/VWF:RCo ratio was able to identify the type 2B variant among an heterogeneous VWD population, previously characterized following the ISTH‐SSC guidelines. Patients/methods Seventy‐six VWD patients and 31 healthy subjects were evaluated by using VWF:Ag, VWF:RCo, and VWF:GPIbM assays. Results The mean (minimum–maximum values) VWF:GPIbM/VWF:RCo ratio was higher in type 2B patients (2.53, 0.84–6.11) than in healthy controls (1.05, 0.87–1.34), type 1 (0.85, 0.51–1.15), 2A (1.20, 0.36–2.82), and 2M (1.07, 0.91–1.38) (P < 0.0001). Type 2B variants were divided into four groups (A, B, C, and D) according to their different multimeric patterns. The mean value of the VWF:GPIbM/VWF:RCo ratio in the four groups showed an increasing trend from group A (1.08) to D (3.69), proportional to the loss of high molecular weight multimers. Among 32 type 2B patients, previously diagnosed with RIPA, 8 (mainly with a type I New York/Malmö phenotype) were not confirmed using the VWF:GPIbM/VWF:RCo ratio. Conclusions Whenever the RIPA test is not feasible, the VWF:GPIbM/VWF:RCo ratio might help to identify severe type 2B VWD patients.